Multiphysics modelling of MICP grouting for drawdown control and curtain stability in confined aquifers with partially penetrating barriers during deep excavation - Sharif Nyanzi Alidekyi; Jianxiu Wang; Weiqiang Pan; Muhammad Arslan Ahmad; Yanxia Long; Naveed Sarwar Abbasi; Aamir Khan Mastoi (Computers and Geotechnics, 2027)

Pathogen-induced physiological reprogramming and systemic dysfunction in plants - Mubashir Sharif; Muhammad Annas Shahid; Mahad Ur-Rehman; Ikhlas Shafique; Muhammad Farooq; Muhammad Amjad Ali (Physiological and Molecular Plant Pathology, 2026)

Spatial distribution and compartmental storage of microplastic particles in a tropical lowland river system (Perak river, Malaysia) - Sarva Mangala Praveena; Muhammad Nifail Sharif; Alif Ilhami Mohd Zamri; Mohd Amir Md Khalid; Mohd Firdaus Mohd Anuar; Vita Pramaningsih; Samuel Abiodun Kehinde (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Monitoring Extent of Mangroves in Coastal Bangladesh from 1980 to 2020: A Remote Sensing-Based Geospatial Analysis - Muhammad Al-Amin Hoque; Maliha Sanzana Misty; Khandaker Tanvir Hossain; Sharif A. Mukul (Small-scale Forestry, 2026)
Mangrove ecosystems play a vital role in coastal protection, biodiversity conservation, and climate regulation, yet their spatiotemporal dynamics within highly geomorphologically active deltaic environments remain insufficiently understood. This study aimed to map long-term changes in mangrove distribution, quantify mangrove gain and loss patterns, identify dominant land-cover transition pathways, and evaluate the influence of erosion–accretion processes on mangrove dynamics in the Meghna Estuary of coastal Bangladesh using a remote sensing-based geospatial framework spanning 1980–2020. Multi-temporal Landsat imagery was processed through standardized pre-processing, NDVI analysis, and supervised Maximum Likelihood land-use/land-cover classification to quantify mangrove extent, spatial trajectories, and gain–loss dynamics. Post-classification change detection and trajectory analysis were employed to evaluate transitions between mangrove, waterbody, vegetation, and agricultural classes. Results reveal a highly dynamic coastal system characterized by alternating phases of mangrove expansion and contraction primarily driven by erosion–accretion processes. Mangrove cover exhibited a net increase of 158.9 km 2 over four decades, with major gains occurred during 1990–1995 and 2000–2005, primarily due to sediment deposition and natural colonization on newly formed mudflats. Conversely, notable declines between 2005 and 2016 were associated with shoreline erosion and channel migration. Land-trajectory analysis highlights dominant waterbody-to-mangrove transitions, emphasizing the importance of geomorphological processes in shaping ecosystem regeneration and resilience. Despite overall expansion, continuous spatial redistribution indicates ecosystem fragility, with gains concentrated on accretion-prone surfaces and losses along erosion-prone margins. The findings provide the first comprehensive four-decade spatial assessment of mangrove dynamics in the Meghna Estuary, offering critical evidence for adaptive coastal management, ecosystem restoration, and nature-based climate mitigation in Bangladesh.

In silico pharmacological evaluation of a multi-epitope vaccine candidate targeting the G1 and G2 glycoproteins of Oropouche virus via TLR3 interaction - Khadija Khawar; Komal Imran; Muhammad Aamir Sharif; Muhammad Naveed; Nantenaina Tombozara; Maha A. Alwaili; ‏Mariam A. Alkhateeb; Seham O. Alsulami (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Engineered biochar as a powerful tool for microplastics removal from wastewater: a critical review - Muhammad Bilal Shakoor; Karolina Mierzyńska; Fakhra Sharif; Piotr Zieliński (Environmental Geochemistry and Health, 2026)

Corrigendum to “Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes” [Fuel 412 (2025) 138022] - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Systematic evaluation of wastewater surveillance of infectious diseases in low- and middle-income countries during the COVID-19 pandemic - Md Pervez Kabir; Asma Safia Disha; Muhammad Mainuddin Patwary; Mahadi Hasan; Sharif Mutasim Billah; Juvair Hossan; Afrin Laila Parvin; Mehedi Hasan; Tyson E. Graber; Egide Kalisa; Robert Delatolla (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes”. [Fuel 412 (2025) 138022. doi: 10.1016/j.fuel.2025.138022] - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

A review on the effects of iron (Fe) on Ulva prolifera: Mechanisms of growth promotion, inhibition, and biochemical responses - Md Mohidul Islam; Sahr Lamin Sumana; Mukhtar Abdullateef Muhammad; Gelena Urgesa Ayana; Shisi Fu; Abubakar Shuaibu; Ahmed E. Elshafey; Yifei Shen; Yuqing Sun; Md. Simul Bhuyan; Md. Enamul Hoq; Touhidul Hoque Shuvo; et al. (Algal Research, 2026)

SARS-CoV-2 antibody responses during the omicron wave in kano, nigeria: Implications for strengthening future vaccine strategies - Bilkisu Ahmed; Jamilu Abubakar Bala; Taysir Ramadan Hafiz; Isah Abubakar Aliyu; Abdulhadi Sale Kumurya; Ibrahim Muhammad Badamasi; Hayatu Saidu; Muhammad Adamu Abbas; Auwal Idris Kabuga; Alhassan Sharif Abdullahi; Bashiru Garba; Al-Mukhtar Yahuza Adamu; et al. (Next Research, 2026)

Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Fe-MIL-101/Ti3C2Tx heterostructures via In-Situ solvothermal strategy for efficient oxygen evolution reaction - Shumaila Bibi; Muhmmad Irfan; Faiza Jan Iftikhar; Inas A. Ahmed; Muhammad Zahid Qureshi; Ahsan Sharif; Shu-Juan Bao; Aziz ur Rehman (Fuel, 2026)

A comprehensive review on nutritional, functional, and clinical perspectives of chia seeds and chia mucilage - Muhammad Arham Rauf; Maira Abdul Razzak; Fatima Waheed; Tabana Naz; Maham Fatima; Tanveer Ahmad; Muhammad Arslan; Usman Mir Khan; Mian Kamran Sharif (Bioactive Carbohydrates and Dietary Fibre, 2026)

α-Pinene alleviates inflammatory responses and oxidative stress in freund’s complete adjuvant induced arthritic rat model and associated risk factors of atherosclerosis - Khadija Ali; Iqral; Ali Sharif; Bushra Akhtar; Ayesha Younas; Muhammad Ali; Muhammad Furqan Akhtar; Muhammad Imran Khan; Ahmed Al-Harrasi; Aftab Ahmad (Inflammopharmacology, 2026)

Greening the future: deep intelligent neural networks-based analysis of green finance in renewable energy and environmental degradation in emerging economies - Hafiz Muhammad Naveed; Yanchun Pan; Arshian Sharif; Muhammad Farhan Bashir; Mamdouh Abdulaziz Saleh Al-Faryan (Environment, Development and Sustainability, 2026)

Review on flexible frameworks: Phosphazene functional polymers powering the future of membranes - Yasir Abbas; Muhammad Waqar Hameed; Zahid Ali; Ghulam Yasin; Kanwal Shabbir; Ijaz Hussain; Muhammad Ahsan Iqbal; Hafiz M. Adeel Sharif; Zhanpeng Wu; Nadeem Baig; Isam H. Aljundi; Niaz Ali Khan; et al. (Chemical Engineering Journal, 2026)

Retraction Note: Trilemma assessment of energy intensity, efficiency, and environmental index: evidence from BRICS countries - Zulifqar Ali Baloch; Qingmei Tan; Nadeem Iqbal; Muhammad Mohsin; Qaiser Abbas; Wasim Iqbal; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2026)

Efficient cadmium sequestration from water using cotton husk biochar and copper oxide nanocomposite: adsorption performance, kinetics, and isotherm modeling - Atika Waqar; Muhammad Farhan; Faiza Sharif; Muhammad Imran; Ghulam Mustafa Shah (Environmental Geochemistry and Health, 2026)

Molecular Characterization of Oculocutaneous Albinism in Consanguineous Pakistani Families: Unraveling Disease-Causing Pathogenic Variants in OCA2 and TYR Genes for Precision Diagnosis - Haiba Kaul; Shagufta Naz; Hafiz Ishfaq Ahmad; Nameerah Saleem; Muhammad Shakil; Sabika Firasat; Bilal Majeed; Saima Sharif; Farzana Rashid; Abdullah Etezaz; Muhammad Umer Khan (Biochemical Genetics, 2026)

Microbial production and biocatalytic docking of pectin lyase for green oil extraction in biorefinery applications - Sikander Ali; Saba Mahboob; Ishtiaq Ahmad; Muhammad Usman Ahmad; Hafiza Kanwal; Sundas Sharif; Khayala Mammadova; Muhammad Arshad (Archives of Microbiology, 2026)

Retraction Note: Environmental efficiency and the role of energy innovation in emissions reduction - Muhammad Khalid Anser; Wasim Iqbal; Umar Suffian Ahmad; Arooj Fatima; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2026)

Hematological, Histological, and NMR Analysis of Meat Quality and Growth Performance of Broilers Fed with Probiotics Bacillus licheniformis-Supplemented Poultry Feed - Basit Ali Khan; Sundas Sharif; Amna Mehdi; Iram Liaqat; Sikander Ali; Asad-ur-Rehman; Liangcai Peng; Sohail Afzal; Muhammad Nauman Aftab (Probiotics and Antimicrobial Proteins, 2026)

Intraspecific and interspecific variation of Salvadora species (S. oleoides Decne. and S. persica L.) along an aridity gradient in dryland ecosystems - Ummar Iqbal; Atta Hussain Sahir; Muhammad Sharif; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf; Sadaf Rafiq; Sana Abid (Trees, 2026)

Microstructural adaptations of snow bush (Aerva javanica (Burm.f.) Juss. Ex Schult.) in desert ecosystems - Sana Abid; Ummar Iqbal; Muhammad Sharif; Sadaf Rafiq; Aisha Sana; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf (The Science of Nature, 2026)

Native Plants as Living Sensors: Tracking Air Pollution in Industrial Zones - Muhammad Sharif; Ummar Iqbal; Abdul Wahab; Muhammad Yousuf; Mehboob Ahmad; Muhammad Sharjeel Arif (International Journal of Environmental Research, 2026)

Synergistic effect of prednisolone and omega-3 fatty acids revealed through in silico, in vitro, and in vivo approaches against APAP-induced mouse model of acute liver injury - Zainab Rehman; Muhammad Ali; Arifa Mehreen; Ghulam Mustafa; Bushra Akhtar; Ali Sharif; Sehrish Murtaza; Muhammd Haroon Hamed; Amina Sagheer; Mahnoor Yamin (Toxicology and Applied Pharmacology, 2026)

Transformation of wet chemically derived ZnGa-LDH to ZnO:GaN nano-alloys for PMS activated wastewater remediation - Yasir Abbas; Kanwal Shabbir; Haider Aziz; Ijaz Hussain; Hafiz M. Adeel Sharif; Muhammad Ahsan Iqbal; Majid Basharat; Haoliang Wang; Niaz Ali Khan (Journal of Environmental Chemical Engineering, 2025)

Enhancing environmental quality and mitigating climate change: a renewable energy policy perspective based on evidence from most polluted European countries - Muhammad Sadiq; Muhammad Atif Nawaz; Fengsheng Chien; Arshian Sharif; Sobia Hanif (Gondwana Research, 2025)

Biomonitoring Vehicular Pollution Using Naturally Occurring Indicator Species Ricinus communis L. (Euphorbiaceae) Along Roadways - Muhammad Faisal Gul; Ummar Iqbal; Muhammad Sharif; Nargis Naz; Farooq Ahmad (Water, Air, & Soil Pollution, 2025)

Phenotypic Characterization and Adaptability of Wild Sugarcane to Diverse Pedospheric and Atmospheric Conditions - Ummar Iqbal; Mehboob Ahmad; Muhammad Sharif; Abdul Wahab; Muhammad Yousuf; Sadaf Rafiq; Sana Abid (Tropical Plant Biology, 2025)

Turn-off Fluorimetric Detection of Fe3+ Metal Ions by a Schiff Base Probe (E)-2-(((2-hydroxy-4-sulfonaphthalen-1-yl) imino) methyl) Benzoic Acid: A Combined Experimental and Theoretical Study - Muhammad Shahbaz; Muhammad Aqib Khurshid; Muhammad Ejaz; Mazhar Amjad Gilani; Maham Saeed; Ayesha Shahzad; Sundas Shahzad; Rashid Masih; Shahzad Sharif (Journal of Fluorescence, 2025)

Addressing agricultural energy poverty to enhance farmers' profitability and productivity: Policy interventions for global food security challenges - Yongming Huang; Qaiser Abbas; Muhammad Sharif (Energy Policy, 2025)

Retraction Note: The nexus between urbanization, renewable energy consumption, financial development, and CO2 emissions: evidence from selected Asian countries - Ahsan Anwar; Avik Sinha; Arshian Sharif; Muhammad Siddique; Shoaib Irshad; Waseem Anwar; Summaira Malik (Environment, Development and Sustainability, 2025)

Ultraviolet processing for mycotoxin mitigation: A sustainable approach to enhancing food safety and security - Abuzar; Hafiz Rizwan Sharif; Rizwan Arshad; Mian Kamran Sharif; Waqas Ashraf; Iahtisham Ul-Haq; Zafarullah Muhammad; Mohamed A. Fahmy; Sameh A. Korma; João M. Rocha (Toxicon, 2025)

Efficient and sustainable transfer hydrogenation and N-formylation of nitroarenes using a facilely synthesized Co₄N/NC nanocatalyst - Anosha Rubab; Md A. Wahab; Ahmed Abdala; Muhammad Sharif; Waqas Ahmed; Manzar Sohail (Journal of Environmental Chemical Engineering, 2025)

Assessing the connectedness between green finance, financial developments, traditional energy consumption, economic growth, population aging and environmental degradation in RECP economies: A deep learning-based analysis - Hafiz Muhammad Naveed; Arshian Sharif; Muhammad Farhan Bashir; Mamdouh Abdulaziz Saleh Al-Faryan; Yanchun Pan (Journal of Environmental Management, 2025)

From scorching sands to survival: adaptive tale of the genus Tribulus (T. longipetalus, T. terrestris and T. pentandrus) in desert ecosystem - Ummar Iqbal; Muhammad Sharif; Sana Abid; Sadaf Rafiq; Abdul Wahab (The Science of Nature, 2025)

Current status, challenges, and opportunities of agroforestry in rice-based mixed farming systems in Northern Bangladesh - Muhammad Ziaul Hoque; Minhaz Ahmed; Sharif Ahmed; Md. Zahid Hasan; Md. Ataur Rahman; Humnath Bhandari (Agroforestry Systems, 2025)

Plant-derived green metal nanoparticles as antibacterial, antifungal, and therapeutic agents: Advances, challenges, and perspectives - Rabia Zafar; Azeem Intisar; Muhammad Imran Din; Ahsan Sharif; Ejaz Ahmed; Adeel Afzal (Bioresource Technology Reports, 2025)

Exploring the complex nexus of climate change, food security, and public health: A scientific perspective through bibliometric analysis - Nurul Izzati Mohd Ali; Nur Syamimi Mohamad; Nurul Izzaty Hassan; Zein Kallas; Muhammad Adzran Che Mustapa; Kuok Choy Lam; Kadaruddin Aiyub; Sharif Shofirun Sharif Ali; Najwa Imani Mohd Ali (Environmental Science & Policy, 2025)

Mapping dengue susceptibility in Dhaka city: a geospatial multi-criteria approach integrating environmental and demographic factors - Muhammad Al-Amin Hoque; Md. Limon Sardar; Sharif A. Mukul; Biswajeet Pradhan (Spatial Information Research, 2025)
Dengue, a rapidly spreading mosquito-borne disease, poses a serious public health threat in tropical cities like Dhaka, Bangladesh—one of the world’s most densely populated megacities. In 2023 alone, Dhaka experienced its worst outbreak, recording 321,179 cases and 1,705 deaths. This study aims to assess dengue susceptibility across Dhaka using a geospatial Multi-Criteria Decision-Making (MCDM) approach. Fourteen environmental and demographic factors were selected, and thematic raster layers were developed and weighted using the Analytical Hierarchy Process (AHP). These layers were integrated to generate spatial dengue susceptibility maps, highlighting risk zones across the city. Findings reveal that southern and southeastern Dhaka, particularly under the South City Corporation, are highly susceptible based on environmental factors. Demographic analysis shows moderate to very high susceptibility in central and southern wards, with population density and proximity to waterlogged areas identified as key drivers. The model was validated through field surveys with 80 stakeholders, with 67.5% agreeing with the susceptibility classifications. This study provides a scalable and transferable framework for dengue risk assessment and can inform targeted interventions in other endemic regions. The results offer critical guidance for urban health planning, vector control, and resource allocation to mitigate dengue and similar vector-borne diseases.

Assessing the anticancer potential of Bergenia ciliata conjugated silk fibroin nanoparticles through histopathological and biomarkers study - Faiza; Shaukat Ali; Muhammad Summer; Faiza Sharif (Journal of Molecular Histology, 2025)

Enhancing Salt Tolerance in Tomato Crop Using Microbial Inoculants - Farheen Islam; Afshan Rahman; Hafiza Farhat; Urooj Muhammad Sharif; Nawal Gul; Areeba Aslam (Journal of Crop Health, 2025)

Structural Traits Driving Water Hyacinth (Eichhornia crassipes) Aggressive Spread and Ecosystem Disruption - Ummar Iqbal; Abdul Wahab; Sadaf Rafiq; Sibgha Noreen; Sana Abid; Muhammad Sharif; Mehboob Ahmad; Muhammad Yousuf (Water, Air, & Soil Pollution, 2025)

Balancing well-being and environment: The moderating role of governance in sustainable development amid environmental degradation - Feng Wang; Seemab Gillani; Arshian Sharif; Muhammad Nouman Shafiq; Umar Farooq (Journal of Environmental Management, 2025)

Rapid and selective E-waste gold extraction from aqua regia by dual redox active-sites of skeleton modulated poly(organo)phosphazenes - Yasir Abbas; Sajjad Ali; Majid Basharat; Hafiz M. Adeel Sharif; Muhammad Ahsan Iqbal; Mohamed Bououdina; Haoliang Wang; Niaz Ali Khan (Chemical Engineering Journal, 2025)

N-Dimethyl chalcone facilitated augmentation of IL-10 and diminution of TNF-α, IL-1β, IL-6, NFκB, and COX-2 in FCA-induced arthritic rat model - Faiza Waseem; Ali Sharif; Maryam Shabbir; Bushra Akhtar; Syed Wadood Ali Shah; Shahnaz; Adeel Arshad; Ejaz Basheer; Muhammad Asif Hanif; Muhammad Ali (Inflammopharmacology, 2025)

Unlocking the biological potential of methyl antcinate A: a new frontier in cancer and inflammation application - Maria Sharif; Muhammad Irfan; Kafila Kousar; Assem Mamurova; Lorena Duarte-Peña; Hector Hernández-Parra; Hernán Cortés; Sheila I. Peña-Corona; Khushbukhat Khan; Solomon Habtemariam; Gerardo Leyva-Gómez; Javad Sharifi-Rad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Biomonitoring and phytoremediation potential of Conocarpus erectus (Buttonwood) for mitigating air pollution from highway traffic - Akkasha Azam; Ummar Iqbal; Zartasha Usman; Muhammad Sharif; Muhammad Faisal Gul; Nargis Naz; Ifrah Nawaz; Farooq Ahmad (Chemosphere, 2025)

Technical and economic assessment of hydrogen production from heavy fuel oil via thermochemical conversion routes - Ali A. Al-Qadri; Usama Ahmed; Shaikh Abdur Razzak; Muhammad Shahbaz; Murid Hussain; Sharif H Zein (Fuel, 2025)

Striving towards green total factor productivity: A bibliometric and systematic literature review for future research agenda - Himja Sharma; Balakrushna Padhi; Arshian Sharif; Muhammad Farhan Bashir (Journal of Environmental Management, 2025)

Thriving in extremes: Adaptability potential of desert cotton Aerva javanica to hyper-arid saline conditions - Ummar Iqbal; Sana Abid; Muhammad Sharif; Sadaf Rafiq; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf (Journal of Arid Environments, 2025)

Unveiling exceptional conduction mechanism and high proton conductivity in amorphous electrolyte for advanced ceramic fuel cells - Touseef Ahmad; Naveed Mushtaq; Hafsa Mansha; Kashf Zaman; Muhammad Khalid; Muhammad Ahsan Masood; Muhammad Shahid Sharif; Yuzheng Lu; Bin Zhu (Fuel, 2025)

Phytoremediation Capacity of Saltwort (Salsola imbricata Forssk.) Determined by Tissue Organization and Physio-biochemical traits under Arid Saline Environments - Ummar Iqbal; Muhammad Sharjeel Arif; Muhammad Sharif; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf; Sadaf Rafiq; Sana Abid (Water, Air, & Soil Pollution, 2025)

Implications of nociceptor receptors and immune modulation: emerging therapeutic targets for autoimmune diseases - Syeda Asloob Fatima; Bushra Akhtar; Ali Sharif; Muhammad Imran Khan; Muhammad Shahid; Fozia Anjum; Fatma Hussain; Aisha Mobashar; Maham Ashraf (Inflammopharmacology, 2025)

Enhancing Wheat Yield and Zinc Biofortification through Synergistic Action of Potent Zinc-Solubilizing Bacteria and Zinc Sulfate in Calcareous Soil - Murad Ali; Iftikhar Ahmed; Munir Hussain Zia; Saira Abbas; Tariq Sultan; Muhammad Sharif (Agricultural Research, 2025)

A citizen science platform to sample beehive sounds for monitoring ANSP - Baizhong Yu; Xinqiu Huang; Muhammad Zahid Sharif; Nayan Di; Fanglin Liu (Journal of Environmental Management, 2025)

Evaluation of Genotype × Environment Interaction and Yield Stability of Cotton (Gossypium hirsutum L) Genotypes Under Heat Stress Conditions - Iram Sharif; Saba Aleem; Jamshaid Ali Junaid; Muqadas Aleem; Khazina Jamshaid; Huma Saleem; Muhammad Rizwan; Shahid Munir Chohan; Saqib Sohail; Saba Akram; Muhammad Zeeshan; Ghulam Sarwar (Journal of Crop Health, 2025)

Natural resources demand, energy transition, and global mineral market: An assessment of BRICS mineral policy - Muhammad Farhan Bashir; Mara Madaleno; Arshian Sharif; Madiha Bashir (Resources Policy, 2025)

Olive oil and castor oil-based self-nanoemulsifying drug delivery system of flurbiprofen can relieve peripheral pain and inflammation through reduction of oxidative stress and inflammatory biomarkers: a comprehensive formulation and pharmacological insights - Mazaghul Basar; Muhammad Imran Khan; Muhammad Furqan Akhtar; Fareeha Anwar; Ammara Saleem; Asadullah Madni; Zulcaif Ahmad; Ali Sharif; Bushra Akhtar; Uzma Shakoor; Aslam Khan (Inflammopharmacology, 2025)

Two-dimensional Bi2Se3 nanosheets synthesis for efficient electrocatalytic production of ammonia from nitrate - Sadeeq Ullah; Aftab Ahmad; Majeed Ur Rehman; Ashfaq Ahmad; Shah Zada; Daxiang Cui; Hafiz Muhammad Adeel Sharif; Lu Li (Journal of Environmental Chemical Engineering, 2024)

Multilayered photo-bioanode for simultaneous conversion of CO2 and industrial refractory organics into bioelectricity in a microbial fuel cell system - Muhammad Ahmad; Maryam Yousaf; Aisha Batool; Hafiz Muhammad Adeel Sharif (Fuel, 2024)

Development of growth curve and estimation of genetic parameters of Nili-Ravi buffalo calves from birth to one year of age through non-linear models - Asad Abbas; Atia Basheer; Moinina Nelphson Kallon; Numan Sharif; Heydar Ghiasi; Tariq Mehmood; Burhane Azam; Anjum Khalique; Muhammad Dawood; Imran Zahoor (Tropical Animal Health and Production, 2024)

Environmental taxes, energy transition and sustainable environmental technologies: A comparative OECD region climate change analysis - Muhammad Farhan Bashir; Arshian Sharif; Marcin W. Staniewski; Beiling Ma; Wenting Zhao (Journal of Environmental Management, 2024)

Optimization of subcritical water extraction for pectin extraction from cocoa pod husks using the response surface methodology - Satria Bhirawa Anoraga; Rosnah Shamsudin; Muhammad Hazwan Hamzah; Suzannah Sharif; Arifin Dwi Saputro; Mohd Salahuddin Mohd Basri (Food Chemistry, 2024)

Unveiling the heterojunction of Fe3O4@MXene nanocatalyst for ultrafast degradation of antibiotics via non-radical pathway - Jintong Huang; Hafiz Muhammad Adeel Sharif; Ayyaz Mahmood; Changping Li (Chemical Engineering Journal, 2024)

Synthesis, Crystal Structure and Fluorimetric Study of 2-phenylphthalazin-1(2H)-one: a Highly Selective Florescent Chemosensor for Detection of Fe3+ and Fe2+ Metal Ions - Shahzad Sharif; Muhammad Shahbaz; Onur Şahin; Muhammad Aqib Khurshid; Maryam Musaffa Anbar; Birra Dar (Journal of Fluorescence, 2024)

Gingerol nanoparticles attenuate complete Freund adjuvant-induced arthritis in rats via targeting the RANKL/OPG signaling pathway - Rida Siddique; Faqir Muhammad; Muhammad Naeem Faisal; Bushra Akhtar; Ammara Saleem; Shaneel Kousar; Ali Sharif; Muhammad Saeed; Safwan Muhammad (Inflammopharmacology, 2024)

Evaluation the Effects of Copper Nanoparticles Dietary Supplementation on Growth Performance, Carcass Characteristics, and Serum Antioxidant Status in Broilers - Bilal Ahmed; Muhammad Sharif; Safdar Hassan; Muhammad Khalid Bashir; Fawwad Ahmad (Biological Trace Element Research, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Retraction Note: The step towards environmental mitigation in Pakistan: do transportation services, urbanization, and financial development matter? - Danish Iqbal Godil; Paiman Ahmad; Muhammad Sajjad Ashraf; Salman Sarwat; Arshian Sharif; Syed Shabib-ul-Hasan; Kittisak Jermsittiparsert (Environmental Science and Pollution Research, 2024)

Unraveling the dynamic nexus between economic complexity, renewable energy consumption, energy imports, and environmental quality in Pakistan - Muhammad Sharif; Farzana Naheed Khan (Environment, Development and Sustainability, 2024)

Estimating economic losses from perceived heat stress in a global south country, Bangladesh - Mondira Bardhan; Muhammad Mainuddin Patwary; Sardar Al Imran; Sharif Mutasim Billah; Mehedi Hasan; Asma Safia Disha; Md Pervez Kabir; Chameli Saha; Md. Najmus Sayadat Pitol; Matthew H.E.M. Browning (Urban Climate, 2024)

Evolving waste management: The impact of environmental technology, taxes, and carbon emissions on incineration in EU countries - Muhammad Imran; Zhang Jijian; Arshian Sharif; Cosimo Magazzino (Journal of Environmental Management, 2024)

Pyridine-2,6-Dicarboxylic Acid As a Facile and Highly Selective “Turn-Off” Fluorimetric Chemosensor for Detection of Cu (II) Ions in Aqueous Media - Javed Hussain Shah; Shahzad Sharif; Muhammad Shahbaz; Bilal Riaz; Sundas Shahzad; Onur Şahin; Khurram Shahzad Munawar; Hijaz Ahmad; Essam A. Al-Ammar (Journal of Fluorescence, 2024)

RETRACTED ARTICLE: Multifaceted role of TRIM21 in inflammation - Sana Tanveer; Ali Afzal; Zaman Gul; Hanan Afzal; Amara Noureen; Muhammad Sharif; Muhammad Babar Khawar (Biologia Futura, 2024)

Ce-TiO2 nanoparticles with surface-confined Ce3+/Ce4+ redox pairs for rapid sunlight-driven elimination of organic contaminants from water - Amna Jamil; Tehzeeb Sawaira; Asghar Ali; Muhammad Awais; Amir Habib; Tajamal Hussain; Ahsan Sharif; Naseer Iqbal; Adeel Afzal (Environmental Nanotechnology, Monitoring & Management, 2024)

Retraction Note: Asymmetric effect of FDI and public expenditure on population health: new evidence from Pakistan based on non-linear ARDL - Saif ur Rahman; Imran Sharif Chaudhry; Muhammad Saeed Meo; Salman Maqsood Sheikh; Sadia Idrees (Environmental Science and Pollution Research, 2024)

Analysing the interplay between energy transition, resource consumption, deforestation, and environmental factors on agricultural productivity: Insights from APEC countries - Zhongmin Zhou; Arshian Sharif; Roula Inglesi-Lotz; Muhammad Farhan Bashir (Journal of Cleaner Production, 2024)

Geopolitical risk, financial development, and renewable energy consumption: empirical evidence from selected industrial economies - Amal Ben Abdallah; Hamdi Becha; Arshian Sharif; Muhammad Farhan Bashir (Environmental Science and Pollution Research, 2024)

Progress in layered double hydroxides (LDHs): Synthesis and application in adsorption, catalysis and photoreduction - Ahmad Farhan; Aman Khalid; Nimra Maqsood; Sidra Iftekhar; Hafiz Muhammad Adeel Sharif; Fei Qi; Mika Sillanpää; Muhammad Bilal Asif (Science of The Total Environment, 2024)

Economic complexity, natural resource abundance and education: Implications for sustainable development in BRICST economies - Siying Li; Huaping Sun; Arshian Sharif; Madiha Bashir; Muhammad Farhan Bashir (Resources Policy, 2024)

Functionalized carbon 1D/2D nanomaterials for effective water desalination: Synthesis, applications and cost issues. An overview - Umar Noor; Muhammad Fayyaz Farid; Ammara Sharif; Amna Saleem; Zubair Nabi; Muhammad Furqan Mughal; Kiran Abbas; Toheed Ahmed (Desalination, 2024)

Redox mediators boost NOx reduction via trade-off electron charges using a cube-shaped (cMn@rGO) catalyst; mechanism and electrochemical study - Hafiz Muhammad Adeel Sharif; Jintong Huang; Kifayatullah Khan; Shahzad Afzal; Changping Li (Chemosphere, 2024)

How do fiscal policies, energy consumption and environmental stringency impact energy transition in the G7 economies: Policy implications for the COP28 - Muhammad Farhan Bashir; Amar Rao; Arshian Sharif; Sudeshna Ghosh; Yanchun Pan (Journal of Cleaner Production, 2024)

Harnessing the synergistic impacts of environmental innovations, financial development, green growth, and ecological footprint through the lens of SDGs policies for countries exhibiting high ecological footprints - Najia Saqib; Muhammad Usman; Ilhan Ozturk; Arshian Sharif (Energy Policy, 2024)

Impact of transportation infrastructure and urbanization on environmental pollution: evidence from novel wavelet quantile correlation approach - Muhammad Usman Malik; Zia ur Rehman; Arshian Sharif; Ahsan Anwar (Environmental Science and Pollution Research, 2023)

The dynamic influence of energy consumption, fiscal policy and green innovation on environmental degradation in BRICST economies - Beiling Ma; Arshian Sharif; Madiha Bashir; Muhammad Farhan Bashir (Energy Policy, 2023)

State-of-the-art analysis of the fuel desulphurization processes: Perspective of CO2 utilization in coal biodesulphurization - Muhammad Ahmad; Maryam Yousaf; Jing-Cheng Han; Shafeeq Ur Rahman; Hafiz Muhammad Adeel Sharif; Linlin Wang; Zhaozhao Tang; Yang Zhou; Yuefei Huang (Chemical Engineering Journal, 2023)

Effect of Dietary Supplementation of Zinc Nanoparticles Prepared by Different Green Methods on Egg Production, Egg Quality, Bone Mineralization, and Antioxidant Capacity in Caged Layers - Safdar Hassan; Muhammad Sharif; Muhammad Aslam Mirza; Muhammad Saif ur Rehman (Biological Trace Element Research, 2023)

Phyto- and bio-management of metal(loid)-contaminated soil by inoculating resistant bacteria: evaluating tolerance of treated rice plant and soil with its efficiency - Zainab Tahir; Muhammad Umar Hayyat; Qaiser Farid Khan; Faiza Sharif; Muhammad Farhan; Laila Shahzad; Gul Zareen Ghafoor (Environmental Science and Pollution Research, 2023)

Adsorption potential of orange rind–based nanosorbents for the removal of cadmium(II) and chromium(VI) from contaminated water - Samia Kanwal; Hafiza Komal Naeem; Fozia Batool; Awais Mirza; Ehab A. Abdelrahman; Gulnaz Sharif; Farah Maqsood; Muhammad Mustaqeem; Allah Ditta (Environmental Science and Pollution Research, 2023)

Heavy metals in five commonly consumed fish species from River Swat, Pakistan, and their implications for human health using multiple risk assessment approaches - Kifayatullah Khan; Maria Zeb; Muhammad Younas; Hafiz Muhammad Adeel Sharif; Muhammad Yaseen; Abdullah G. Al-Sehemi; Yasar N. Kavil; Noor Samad Shah; Xianghui Cao; Afsheen Maryam; Muhammad Qasim (Marine Pollution Bulletin, 2023)

Recent developments in designing Cu-based electrocatalysts and advanced strategies for electrochemical nitrate reduction to ammonia - Sadeeq Ullah; Shiyong Wang; Changping Li; Amin Ullah Jan; Fei Zhan; Hafiz Muhammad Adeel Sharif; Qingling Liu; Gang Wang (Journal of Environmental Chemical Engineering, 2023)

Strategic analysis on development of simultaneous adsorption and catalytic biodegradation over advanced bio-carriers for zero-liquid discharge of industrial wastewater - Jing-Cheng Han; Muhammad Ahmad; Maryam Yousaf; Shafeeq Ur Rahman; Hafiz Muhammad Adeel Sharif; Yang Zhou; Bo Yang; Yuefei Huang (Chemosphere, 2023)

Impact of biochar amendments on copper mobility, phytotoxicity, photosynthesis and mineral fluxes on (Zea mays L.) in contaminated soils - Zainul Abideen; Hans-Werner Koyro; Faisal Zulfiqar; Anam Moosa; Sarwat Ghulam Rasool; Muhammad Zaheer Ahmad; Muhammad Ahsan Altaf; Nadia Sharif; Ali El-Keblawy (South African Journal of Botany, 2023)

Process design, simulation, and techno-economic analysis of integrated production of furfural and glucose derived from palm oil empty fruit bunches - Muhammad Zafran Raja Mohammed; Zi Wei Ng; Aditya Putranto; Zong Yang Kong; Jaka Sunarso; Muhammad Aziz; Sharif H. Zein; Jannata Giwangkara; Ivan Butar (Clean Technologies and Environmental Policy, 2023)

The role of sustainable energy utility, natural resource utilization and waste management in reducing energy poverty: Evidence from South Asian countries - Fengsheng Chien; Muhammad Sadiq; Li Li; Arshian Sharif (Utilities Policy, 2023)

Construction and elucidation of zerovalent iron@terephthalic acid/iron oxide catalyst to activate peroxymonosulfate for accelerating and long-lasting NOx removal - Hafiz Muhammad Adeel Sharif; Muhammad Bilal Asif; Yuwei Wang; Kifayatullah Khan; Yang Cai; Xu Xiao; Changping Li (Chemical Engineering Journal, 2023)

Pterostilbene reduces the progression of atopic dermatitis via modulating inflammatory and oxidative stress biomarkers in mice - Yasmin Bangash; Ammara Saleem; Muhammad Furqan Akhtar; Fareeha Anwar; Bushra Akhtar; Ali Sharif; Muhammad Imran Khan; Aslam Khan (Inflammopharmacology, 2023)

Pollution Haven or Halo? How European countries leverage FDI, energy, and human capital to alleviate their ecological footprint - Najia Saqib; Ilhan Ozturk; Muhammad Usman; Arshian Sharif; Asif Razzaq (Gondwana Research, 2023)

Expression of pro-inflammatory cytokines (IL-6 & IL-18) exacerbate the risk of diabetic nephropathy in the Pakistani population - Maha Maqsood; Saima Sharif; Shagufta Naz; Tasnim Farasat; Farkhanda Manzoor; Maqsood Cheema; Muhammad Saqib (Molecular Biology Reports, 2023)

Chitosan Polymerized Silica Composite as a Potential Silicon Source: Modulation on Antioxidant Enzymes, Ionic Homeostasis, and Grain Quality in Maize Plants Under Na+ Stress - Waqas-ud-Din Khan; Faiza Sharif; Muhammad Asif Naeem; Muhammad Ansar Farooq; Zafar Siddiq; Muhammad Imran (Journal of Plant Growth Regulation, 2023)

Reproductive and metabolic toxic effects of polystyrene microplastics in adult female Wistar rats: a mechanistic study - Anam Saeed; Muhammad Furqan Akhtar; Ammara Saleem; Bushra Akhtar; Ali Sharif (Environmental Science and Pollution Research, 2023)

Dominance of bacillus sp. alter microbiological and nutritional quality and improve aerobic stability of the corn silage - Smayia Sharif; Nafeesa Qudsia Hanif; Shakira Ghazanfar; Muhammad Imran; Mohammed A. E. Naiel; Mahmoud Alagawany (Rendiconti Lincei. Scienze Fisiche e Naturali, 2023)

“Ficus johannis Boiss. leaves ethanolic extract ameliorate streptozotocin-induced diabetes in rats by upregulating the expressions of GCK, GLUT4, and IGF and downregulating G6P” - Afshan Asghar; Ali Sharif; Sana Javaid Awan; Bushra Akhtar; Muhammad Furqan Akhtar; Sajid Ali; Shahnaz (Environmental Science and Pollution Research, 2023)

Quercetin-loaded chitosan nanoparticles ameliorate adjuvant-induced arthritis in rats by regulating anti-oxidant enzymes and downregulating pro- and inflammatory cytokines - Abdul Hannan; Bushra Akhtar; Ali Sharif; Fozia Anjum; Imran Pasha; Ahrar Khan; Muhammad Furqan Akhtar; Ammara Saleem (Inflammopharmacology, 2023)

Dynamic linkages between Islamic equity indices, oil prices, gold prices, and news-based uncertainty: New insights from partial and multiple wavelet coherence - Muhammad Asif Khan; Farhad Khan; Arshian Sharif; Muhammad Tahir Suleman (Resources Policy, 2023)

The role of clean and unclean energy resources in inspecting N-shaped impact of industrial production on environmental quality: A case of high polluting economies - Jinchao Gao; Muhammad Shahid Hassan; Rukhsana Kalim; Arshian Sharif; Tarek Tawfik Yousef Alkhateeb; Haider Mahmood (Resources Policy, 2023)

Spontaneous intra-electron transfer within rGO@Fe2O3-MnO catalyst promotes long-term NOx reduction at ambient conditions - Hafiz Muhammad Adeel Sharif; Muhammad Bilal Asif; Yuwei Wang; Ya-Nan Hou; Bo Yang; Xu Xiao; Changping Li (Journal of Hazardous Materials, 2023)

Reducing environmental pollution by organisational citizenship behaviour in hospitality industry: the role of green employee involvement, performance management and dynamic capability - Ataul Karim Patwary; Arshian Sharif; Roslizawati Che Aziz; Mohamad Ghozali Bin Hassan; Arsalan Najmi; Muhammad Khalilur Rahman (Environmental Science and Pollution Research, 2022)

Pterostilbene improves CFA-induced arthritis and peripheral neuropathy through modulation of oxidative stress, inflammatory cytokines and neurotransmitters in Wistar rats - Ayesha Amin; Muhammad Furqan Akhtar; Ammara Saleem; Ali Sharif; Shahid Shah; Muhammad Imran Khan; Fareeha Anwar; Ghulam Abbas; Hafiz Muhammad Zubair; Muhammad Farhan Sohail (Inflammopharmacology, 2022)

Monitoring honeybees (Apis spp.) (Hymenoptera: Apidae) in climate-smart agriculture: A review - Muhammad Zahid Sharif; Nayan Di; Fanglin Liu (Applied Entomology and Zoology, 2022)

Human health risk estimation of antibiotics transferred from wastewater and soil to crops - Nazish Mohy-u-Din; Muhammad Farhan; Abdul Wahid; Lena Ciric; Faiza Sharif (Environmental Science and Pollution Research, 2022)

Mechanistic insights on the possible protective role of polyphenols extracted from Tamarix aphylla aerial parts against sodium arsenite-induced hepatotoxicity in rats - Shaher Bano; Ali Sharif; Bushra Akhtar; Mohamed M. Abdel-Daim; Muhammad Furqan Akhtar; Faiza Liaqat Ali (Environmental Science and Pollution Research, 2022)

Integration of renewable energy and technological innovation in realizing environmental sustainability: the role of human capital in EKC framework - Najia Saqib; Arshian Sharif; Asif Razzaq; Muhammad Usman (Environmental Science and Pollution Research, 2022)

A matter of the beehive sound: Can honey bees alert the pollution out of their hives? - Baizhong Yu; Xinqiu Huang; Muhammad Zahid Sharif; Xueli Jiang; Nayan Di; Fanglin Liu (Environmental Science and Pollution Research, 2022)

Point prevalence survey to estimate antimicrobial use in a tertiary care university hospital in Pakistan using WHO methodology: findings and implications - Muhammad Sharif; Sana Aslam; Zikria Saleem (Infectious Diseases, 2022)

Heavy metal pollution in the soil of a riverine basin: distribution, source, and potential hazards - Kifayatullah Khan; Abdul Mohsin; Hafiz Muhammad Adeel Sharif; Afsheen Maryam; Jafar Ali; Xu Li; Sobhy Mostafa Ibrahim; Muhammad Ayaz; Yunqiao Zhou; Muhammad Younas (Environmental Monitoring and Assessment, 2022)

Toxicity of selected organophosphate and pyrethroid insecticides against larval and adult stages of Culex quinquefasciatus - Muhammad Zubair; Hafiz Azhar Ali Khan; Waseem Akram; Khurram Zia; Rana Muhammad Naeem Ahsan; Malik Muhammad Shahbaz Sharif; Huma Qamar; Muhammad Kamil Malik (International Journal of Tropical Insect Science, 2022)

Rep-PCR Analyses Reveal Genetic Variation of Ralstonia solanacearum Causing Wilt of Solanaceaous Vegetables in Bangladesh - Md. Mosharraf Hossain; Md. Mostafa Masud; Muhammad Iqbal Hossain; Mohammad Mahbubul Haque; Mohammad Sharif Uddin; Md. Zahangir Alam; Md. Rashidul Islam (Current Microbiology, 2022)

Efficient photocatalytic degradation of nitrobenzene by copper-doped TiO2: kinetic study, degradation pathway, and mechanism - Tehmina Akhtar; Habib Nasir; Effat Sitara; Syeda Aqsa Batool Bukhari; Sharif Ullah; Rana Muhammad Arslan Iqbal (Environmental Science and Pollution Research, 2022)

ATP-binding cassette transporters expression profiling revealed its role in the development and regulating stress response in Solanum tuberosum - Madiha Zaynab; Zongkang Wang; Athar Hussain; Khalida Bahadar; Mateen Sajid; Yasir Sharif; Muhammad Azam; Kalsoom Sughra; Muhammad Ammar Raza; Khalid Ali Khan; Shuangfei Li (Molecular Biology Reports, 2022)

Methotrexate-loaded biodegradable nanoparticles exert anti-arthritic effect by downregulating pro-inflammatory cytokines in Freund’s complete adjuvant-induced arthritic rats - Muhammad Usman Saleem; Faqir Muhammad; Ali Sharif; Muhammad Imran Arshad; Kanwal Akhtar; Yasir Javed; Bushra Akhtar (Inflammopharmacology, 2022)

RETRACTED ARTICLE: The nexus between urbanization, renewable energy consumption, financial development, and CO2 emissions: evidence from selected Asian countries - Ahsan Anwar; Avik Sinha; Arshian Sharif; Muhammad Siddique; Shoaib Irshad; Waseem Anwar; Summaira Malik (Environment, Development and Sustainability, 2022)

3-Dimensional membrane capsules: Synthesis modulations for the remediation of environmental pollutants – A critical review - Imran Ali; Juying Li; Changsheng Peng; Muhammad Qasim; Zahid M. Khan; Iffat Naz; Muhammad Sultan; Muhammad Rauf; Waheed Iqbal; Hafiz Muhammad Adeel Sharif (Critical Reviews in Environmental Science and Technology, 2022)

Validation of environmental Philips curve in Pakistan: a fresh insight through ARDL technique - Arsalan Tanveer; Huaming Song; Muhammad Faheem; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Asymmetric effect of FDI and public expenditure on population health: new evidence from Pakistan based on non-linear ARDL - Saif ur Rahman; Imran Sharif Chaudhry; Muhammad Saeed Meo; Salman Maqsood Sheikh; Sadia Idrees (Environmental Science and Pollution Research, 2022)

Staged energy and water quality optimization for large water distribution systems - Muhammad Nadeem Sharif; Ezzeddin Bakhtavar; Husnain Haider; Guangji Hu; Kasun Hewage; Rehan Sadiq (Environmental Monitoring and Assessment, 2022)

Moderating role of institutional quality in validation of pollution haven hypothesis in BRICS: a new evidence by using DCCE approach - Imran Sharif Chaudhry; Weihua Yin; Syed Ahtsham Ali; Muhammad Faheem; Qaiser Abbas; Fatima Farooq; Saeed Ur Rahman (Environmental Science and Pollution Research, 2022)

Isolation and molecular characterization of Adenovirus in suspected acute flaccid paralysis patients: A preliminary report from Pakistan - Zainab Khattak; Aamer Ali Shah; Syed Sohail Zahoor Zaidi; Nayab Mahmood; Muhammad Masroor Alam; Salmaan Sharif; Ribqa Akhtar; Yasir Arshid; Muhammad Suleman Rana (Archives of Virology, 2022)

The dynamic impact of renewable energy sources on environmental economic growth: evidence from selected Asian economies - Muhammad Khalid Anser; Muhammad Usman; Muhammad Sharif; Sana Bashir; Malik Shahzad Shabbir; Ghulam Yahya Khan; Lydia Bares Lopez (Environmental Science and Pollution Research, 2022)

How precious metal and energy resources interact with clean energy stocks? Fresh insight from the novel ARDL technique - Munaza Bibi; Muhammad Kamran Khan; Sobia Shujaat; Danish Iqbal Godil; Arshian Sharif; Muhammad Khalid Anser (Environmental Science and Pollution Research, 2022)

Gibberellic acid and urease inhibitor optimize nitrogen uptake and yield of maize at varying nitrogen levels under changing climate - Ikram Ullah; Khadim Dawar; Muhammad Tariq; Muhammad Sharif; Shah Fahad; Muhammad Adnan; Haroon Ilahi; Taufiq Nawaz; Mukhtar Alam; Aman Ullah; Muhammad Arif (Environmental Science and Pollution Research, 2022)

Cyperus iria aqueous-ethanol extract ameliorated hyperglycemia, oxidative stress, and regulated inflammatory cytokines in streptozotocin-induced diabetic rats - Myeda Saeed; Ali Sharif; Saeed Ul Hassan; Bushra Akhtar; Faqir Muhammad; Maryam Malik (Environmental Science and Pollution Research, 2022)

Disaggregated renewable energy sources in mitigating CO2 emissions: new evidence from the USA using quantile regressions - Arshian Sharif; Mita Bhattacharya; Sahar Afshan; Muhammad Shahbaz (Environmental Science and Pollution Research, 2021)

Correction to: Does globalization affect the green economy and environment? The relationship between energy consumption, carbon dioxide emissions, and economic growth - Muhammad Khalid Anser; Muhammad Usman; Danish Iqbal Godil; Malik Shahzad Shabbir; Arshian Sharif; Mosab Ismail Tabash; Lydia Bares Lopez (Environmental Science and Pollution Research, 2021)

Moving towards sustainability: how do natural resources, financial development, and economic growth interact with the ecological footprint in Malaysia? A dynamic ARDL approach - Muhammad Kamran Khan; Farwa Abbas; Danish Iqbal Godil; Arshian Sharif; Zafar Ahmed; Muhammad Khalid Anser (Environmental Science and Pollution Research, 2021)

Does globalization affect the green economy and environment? The relationship between energy consumption, carbon dioxide emissions, and economic growth - Muhammad Khalid Anser; Muhammad Usman; Danish Iqbal Godil; Malik Shahzad Shabbir; Arshian Sharif; Mosab I. Tabash; Lydia Bares Lopez (Environmental Science and Pollution Research, 2021)

Copper Nanoparticles as Growth Promoter, Antioxidant and Anti-Bacterial Agents in Poultry Nutrition: Prospects and Future Implications - Muhammad Sharif; Muhammad Aziz-ur Rahman; Bilal Ahmed; Rao Zahid Abbas; Faiz-ul Hassan (Biological Trace Element Research, 2021)

Demographic, psychological, and environmental factors affecting student’s health during the COVID-19 pandemic: on the rocks - Muhammad Khalid Anser; Muhammad Sharif; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Khalid Zaman; Muhammad Moinuddin Qazi Abro; Ahmad Kabbani (Environmental Science and Pollution Research, 2021)

RETRACTED ARTICLE: The step towards environmental mitigation in Pakistan: do transportation services, urbanization, and financial development matter? - Danish Iqbal Godil; Paiman Ahmad; Muhammad Sajjad Ashraf; Salman Sarwat; Arshian Sharif; Syed Shabib-ul-Hasan; Kittisak Jermsittiparsert (Environmental Science and Pollution Research, 2021)

Correction to: Assessing the integration of solar power projects: SWOT-based AHP–F-TOPSIS case study of Turkey - Muhammad Khalid Anser; Muhammad Mohsin; Qaiser Abbas; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2020)

Correction to: Optimal oil stockpiling, peak oil, and general equilibrium: case study of South Asia (oil importers) and Middle East (oil supplier) - Muhammad Khalid Anser; Qaiser Abbas; Imran Sharif Chaudhry; Arman Khan (Environmental Science and Pollution Research, 2020)

Correction to: Environmental efficiency and the role of energy innovation in emissions reduction - Muhammad Khalid Anser; Wasim Iqbal; Umar Suffian Ahmad; Arooj Fatima; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2020)

RETRACTED ARTICLE: Trilemma assessment of energy intensity, efficiency, and environmental index: evidence from BRICS countries - Zulifqar Ali Baloch; Qingmei Tan; Nadeem Iqbal; Muhammad Mohsin; Qaiser Abbas; Wasim Iqbal; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2020)

Assessing the integration of solar power projects: SWOT-based AHP–F-TOPSIS case study of Turkey - Muhammad Khalid Anser; Muhammad Mohsin; Qaiser Abbas; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2020)

RETRACTED ARTICLE: Environmental efficiency and the role of energy innovation in emissions reduction - Muhammad Khalid Anser; Wasim Iqbal; Umar Suffian Ahmad; Arooj Fatima; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2020)

Cardiac toxicity of heavy metals (cadmium and mercury) and pharmacological intervention by vitamin C in rabbits - Shaukat Ali; Zubia Awan; Shumaila Mumtaz; Hafiz Abdullah Shakir; Farooq Ahmad; Mazhar Ulhaq; Hafiz Muhammad Tahir; Muhammad Siddique Awan; Saima Sharif; Muhammad Irfan; Muhammad Adeeb Khan (Environmental Science and Pollution Research, 2020)

Analyzing carbon emission transfer network structure among provinces in China: new evidence from social network analysis - Licheng Sun; Lin Qin; Farhad Taghizadeh-Hesary; Jijian Zhang; Muhammad Mohsin; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2020)

Optimal oil stockpiling, peak oil, and general equilibrium: case study of South Asia (oil importers) and Middle East (oil supplier) - Muhammad Khalid Anser; Qaiser Abbas; Imran Sharif Chaudhry; Arman Khan (Environmental Science and Pollution Research, 2020)

Genome-Wide Identification of Malectin/Malectin-Like Domain Containing Protein Family Genes in Rice and Their Expression Regulation Under Various Hormones, Abiotic Stresses, and Heavy Metal Treatments - Xiu-Qing Jing; Abdullah Shalmani; Meng-Ru Zhou; Peng-Tao Shi; Izhar Muhammad; Yi Shi; Rahat Sharif; Wen-Qiang Li; Wen-Ting Liu; Kun-Ming Chen (Journal of Plant Growth Regulation, 2020)

Vulnerability, well-being, and livelihood adaptation under changing environmental conditions: a case from mountainous region of Pakistan - Laila Shahzad; Arifa Tahir; Faiza Sharif; Waqas Ud Din Khan; Muhammad Ansar Farooq; Azhar Abbas; Zulfiqar Ahmad Saqib (Environmental Science and Pollution Research, 2019)

Salinity stress in cotton: effects, mechanism of tolerance and its management strategies - Iram Sharif; Saba Aleem; Jehanzeb Farooq; Muhammad Rizwan; Abia Younas; Ghulam Sarwar; Shahid Munir Chohan (Physiology and Molecular Biology of Plants, 2019)

Prevalence and current therapy in chronic liver disorders - Muhammad Daniyal; Muhammad Akram; Rida Zainab; Naveed Munir; Aamir Sharif; Syed Muhammad Ali Shah; Bin Liu; Wei Wang (Inflammopharmacology, 2019)

Idolization and ramification between globalization and ecological footprints: evidence from quantile-on-quantile approach - Arshian Sharif; Sahar Afshan; Muhammad Asif Qureshi (Environmental Science and Pollution Research, 2019)

Liming induces carbon dioxide (CO2) emission in PSB inoculated alkaline soil supplemented with different phosphorus sources - Muhammad Adnan; Zahir Shah; Muhammad Sharif; Hidayatur Rahman (Environmental Science and Pollution Research, 2018)

Association of textile industry effluent with mutagenicity and its toxic health implications upon acute and sub-chronic exposure - Muhammad Furqan Akhtar; Muhammad Ashraf; Aqeel Javeed; Aftab Ahmad Anjum; Ali Sharif; Mohammad Saleem; Ghulam Mustafa; Moneeb Ashraf; Ammara Saleem; Bushra Akhtar (Environmental Monitoring and Assessment, 2018)

A measles outbreak in Sindh, Pakistan caused by a genotype B3 virus - Syed Sohail Zahoor Zaidi; Abdul Hameed; Naeem Ali; Massab Umair; Muhammad Masroor Alam; Muhammad Suleman Rana; Salmaan Sharif; Uzma Bashir Aamir; Shahzad Shaukat; Mehar Angez; Adnan Khurshid; Ribqa Akhtar; et al. (Archives of Virology, 2017)

Risk-based framework for optimizing residual chlorine in large water distribution systems - Muhammad Nadeem Sharif; Ashraf Farahat; Husnain Haider; Muhammad A. Al-Zahrani; Manuel J. Rodriguez; Rehan Sadiq (Environmental Monitoring and Assessment, 2017)

Oxidative stress responses in Wistar rats on subacute exposure to pharmaceutical wastewater - Ali Sharif; Muhammad Ashraf; Aqeel Javeed; Aftab Ahmed Anjum; Muhammad Furqan Akhtar; Bushra Akhtar; Ammara Saleem (Environmental Science and Pollution Research, 2016)

Optimization of chlorination boosters in drinking water distribution network for Al-Khobar City in Saudi Arabia - Muhammad Nadeem Sharif; Ashraf Farahat; Muhammad A. Al-Zahrani; Nilufar Islam; Manuel J. Rodriguez; Rehan Sadiq (Arabian Journal of Geosciences, 2016)

Toxicity Appraisal of Untreated Dyeing Industry Wastewater Based on Chemical Characterization and Short Term Bioassays - Muhammad Furqan Akhtar; Muhammad Ashraf; Aqeel Javeed; Aftab Ahmad Anjum; Ali Sharif; Ammara Saleem; Bushra Akhtar; Abdul Muqeet Khan; Imran Altaf (Bulletin of Environmental Contamination and Toxicology, 2016)

Pharmaceutical wastewater being composite mixture of environmental pollutants may be associated with mutagenicity and genotoxicity - Ali Sharif; Muhammad Ashraf; Aftab Ahmed Anjum; Aqeel Javeed; Imran Altaf; Muhammad Furqan Akhtar; Mateen Abbas; Bushra Akhtar; Ammara Saleem (Environmental Science and Pollution Research, 2016)

A novel protein quality control mechanism contributes to heat shock resistance of worldwide‐distributed P seudomonas aeruginosa clone C strains - Changhan Lee; Edvard Wigren; Janja Trček; Verena Peters; Jihong Kim; Muhammad Sharif Hasni; Manfred Nimtz; Ylva Lindqvist; Chankyu Park; Ute Curth; Heinrich Lünsdorf; Ute Römling (Environmental Microbiology, 2015)
Summary P seudomonas aeruginosa is a highly successful nosocomial pathogen capable of causing a wide variety of infections with clone C strains most prevalent worldwide. In this study, we initially characterize a molecular mechanism of survival unique to clone C strains. We identified a P . aeruginosa clone C ‐specific genomic island ( PACGI ‐1) that contains the highly expressed small heat shock protein sHsp 20c, the founding member of a novel subclass of class B bacterial small heat shock proteins. sHsp 20c and adjacent gene products are involved in resistance against heat shock. Heat stable sHsp 20c is unconventionally expressed in stationary phase in a wide temperature range from 20 to 42°C. Purified sHsp 20c has characteristic features of small heat shock protein class B as it is monodisperse, forms sphere‐like 24‐meric oligomers and exhibits significant chaperone activity. As the P . aeruginosa clone C population is significantly more heat shock resistant than genetically unrelated P . aeruginosa strains without sHsp20c, the horizontally acquired shsp20c operon might contribute to the survival of worldwide‐distributed clone C strains.

Silicon (Si) alleviates cotton (Gossypium hirsutum L.) from zinc (Zn) toxicity stress by limiting Zn uptake and oxidative damage - Shad Ali Anwaar; Shafaqat Ali; Skhawat Ali; Wajid Ishaque; Mujahid Farid; Muhammad Ahsan Farooq; Ullah Najeeb; Farhat Abbas; Muhammad Sharif (Environmental Science and Pollution Research, 2015)

Rice Bran: A Novel Functional Ingredient - Mian Kamran Sharif; Masood Sadiq Butt; Faqir Muhammad Anjum; Saima Hafiz Khan (Critical Reviews in Food Science and Nutrition, 2014)

Feeding value of urea molasses-treated wheat straw ensiled with fresh cattle manure for growing crossbred cattle calves - Muhammad Sarwar; Muhammad A. Shahzad; Mahr U. Nisa; Danish Afzal; Muhammad Sharif; Hafiz A. Saddiqi (Tropical Animal Health and Production, 2011)

A pharmacological and toxicological evaluation of Haloxylon recurvum - Abdul Wahab; Ejaz Ahmed; Sarfraz Ahmad Nawaz; Ahsan Sharif; Rizwan Ul Haq; Abdul Malik; Muhammad Iqbal Choudhary; Mohsin Raza (Natural Product Research, 2008)

Chymotrypsin inhibitory constituents from Haloxylon recurvum - Ejaz Ahmed; Abdul Malik; Nighat Afza; Naheed Riaz; Itrat Anis; Ahsan Sharif; Sadia Farheen; Muhammad Arif Lodhi; Muhammad Iqbal Choudhary (Natural Product Research, 2007)

Genetic relationship in Vigna mungo (L.) Hepper and V. radiata (L.) R. Wilczek based on morphological traits and SDS-PAGE - Abdul Ghafoor; Zahoor Ahmad; Afsari Sharif Qureshi; Muhammad Bashir (Euphytica, 2002)